1992
DOI: 10.21273/hortsci.27.5.453
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Micropropagation of 54 Species from 15 Genera of Bamboo

Abstract: Fifty-four out of 67 species of bamboo tested were successfully propagated in vitro. For nearly every species, multiple shoots were produced from axillary buds on stem node segments cultured on Murashige and Skoog medium containing BA. In a very few species plants could be regenerated adventitiously from callus. This method of propagation was not very efficient or reliable. Rooting occurred in media containing NAA at 2.7 to 5.4 μM. Several species could be stored in vitro on half-strength medium at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…To reduce initial contamination of explants it was necessary to combine standard disinfection procedures involving the use of NaOCl (Yeh and Chang 1986;Prutpongse and Gavinlertvatana 1992) with pre-treatments containing Extran, Agri-mycin and Benomyl. Extran, a product commonly used to disinfect laboratory instruments and surfaces, was previously used in com- Fig.…”
Section: Culture Initiationmentioning
confidence: 99%
See 3 more Smart Citations
“…To reduce initial contamination of explants it was necessary to combine standard disinfection procedures involving the use of NaOCl (Yeh and Chang 1986;Prutpongse and Gavinlertvatana 1992) with pre-treatments containing Extran, Agri-mycin and Benomyl. Extran, a product commonly used to disinfect laboratory instruments and surfaces, was previously used in com- Fig.…”
Section: Culture Initiationmentioning
confidence: 99%
“…Bud sprouting and shoot multiplication BAP (1-12 mg l -1 ) has been very effective in inducing sprouting of axillary buds in several bamboo species belonging to different genera (Prutpongse and Gavinlertvatana 1992;Ramanayake and Yakandawala 1997;Ravikumar et al 1998;Bag et al 2000). Marulanda et al (2002) obtained best results in G. angustifolia with 1.0 mg l -1 BAP (7.16% of the explants sprouted), but they did not evaluate higher concentrations.…”
Section: Culture Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Most species flower after long periods of vegetative growth that range from 3 to more than 120 years (Janzen, 1976;John and Nadgauda, 1999). The results of several studies (Nadgauda et al, 1990;Chambers et al, 1991;Prutpongse and Gavinlertvatana, 1992;Rout and Das, 1994;Lin and Chang, 1998;Gielis et al, 2001;Ramanayake et al, 2001;Lin et al, 2003aLin et al, , 2004 showed that plant tissue culture systems can shorten the juvenile stage of the bamboo life cycle and induce in vitro flowering of these vegetative shoots within a few months. When the medium contains cytokinin, the bamboo can flower in vitro.…”
Section: Introductionmentioning
confidence: 99%